OIT3 serves as a novel biomarker of hepatocellular carcinoma by mediating ferroptosis via regulating the arachidonic acid metabolism - Wen, Jie; Aili, Abudureyimujiang; Yan, Yao Xue; Lai, YuLin; Niu, Shaoqing; He, Shasha; Zhang, Xiaokai; Zhang, Guixiong; Li, Jiaping (Frontiers in Oncology, 2022)
1Background: Previous studies indicated that OIT3 was a liver-specific gene with abnormal expression in HCC. We aimed to examine the function and specific mechanism of OIT3 in HCC. Methods: Herein, the expression of OIT3 in HCC was validated with bioinformatic analyses and tissue microarray via immunohistochemistry. The biofunctions of OIT3 in HCC were determined in vitro and in vivo. The mechanism was confirmed by RNA-Sequence and Western blotting. The uni- and multivariate analyses were applied to dissect the independent predictors of HCC. Results: According to our results, low expression of OIT3 could be observed in HCC and predicted a poor clinical outcome. Ectopic expression of OIT3 may inhibit the proliferation, migration and invasion abilities of HCC cells. Mechanistically, OIT3 upregulated the expression of ALOX15 and CYP4F3 to induce arachidonic acid increase, ROS accumulation, and lipid peroxidation, eventually led to the ferroptosis. OIT3 was validated as a prognostic predictor for HCC patients. Conclusions: Our findings demonstrated a novel role for OIT3 in the process of tumorigenesis of HCC. OIT3 inhibited reproliferation, migration and invasion abilities of HCC cells by triggering ferroptosis, indicating that OIT3 could serve as a potential biomarker in HCC.